Design, Synthesis, Antimycobacterial Evaluation, and In Silico Studies of 3-(Phenylcarbamoyl)-pyrazine-2-carboxylic Acids - Semelková, Lucia; Janošcová, Petra; Fernandes, Carlos; Bouz, Ghada; Janďourek, Ondřej; Konečná, Klára; Paterová, Pavla; Navrátilová, Lucie; Kuneš, Jiří; Doležal, Martin; Zitko, Jan (Molecules (Basel, Switzerland), 2017)
Pyrazinamide, the first-line antitubercular drug, has been regarded the basic component of tuberculosis treatment for over sixty years. Researchers have investigated its effect on Mycobacterium tuberculosis for this long time, and as a result, new potential targets of pyrazinamide or its active form, pyrazinoic acid, have been found. We have designed and prepared 3-(phenyl-carbamoyl)pyrazine-2-carboxylic acids as more lipophilic derivatives of pyrazinoic acid. We also prepared methyl and propyl derivatives as prodrugs with further increased lipophilicity. Antimycobacterial, antibacterial and antifungal growth inhibiting activity was investigated in all prepared compounds. 3-[(4-Nitrophenyl)carbamoyl]pyrazine-2-carboxylic acid (16) exerted high antimycobacterial activity against Mycobacterium tuberculosis H37Rv with MIC = 1.56 μg·mL-1 (5 μM). Propyl 3-{[4-(trifluoromethyl)phenyl]carbamoyl}pyrazine-2-carboxylate (18a) showed also high antimycobacterial activity against Mycobacterium tuberculosis H37Rv with MIC = 3.13 μg·mL-1. In vitro cytotoxicity of the active compounds was investigated and no significant cytotoxic effect was observed. Based to structural similarity to known inhibitors of decaprenylphosphoryl-β-d-ribose oxidase, DprE1, we performed molecular docking of the prepared acids to DprE1. These in silico experiments indicate that modification of the linker connecting aromatic parts of molecule does not have any negative influence on the binding.
Keywords: Antifungal Agents; pyrazinoic acid; Bacterial Proteins; Structure-Activity Relationship; pyraziny; molekulární struktura; Computer Simulation; antibakteriální látky; Molecular Structure; racionální návrh léčiv; Microbial Sensitivity Tests; antifungální látky; pyrazinamide; Molecular Docking Simulation; antimycobacterial activity; alkoholoxidoreduktasy; RpsA; Alcohol Oxidoreductases; DprE1; vztahy mezi strukturou a aktivitou; simulace molekulového dockingu; lidé; cytotoxicity; Anti-Bacterial Agents; Humans; mikrobiální testy citlivosti; bakteriální proteiny; Drug Design; počítačová simulace; anilides; Pyrazines; Mycobacterium tuberculosis